Предмет: Алгебра,
автор: stapanmatyha
Розв'яжіть рівняння (x2+3x)2-2(x2+3x)-8=0 методом заміни змінних.
Ответы
Автор ответа:
0
Ответ: (-2;-1;-4;1).
Объяснение:
(x²+3x)²-2(x²+3x)-8=0;
Обозначим x²+3x =t. Тогда
t²-2t-8=0;
По т. Виета
t1+t2 = 2;
t1*t2=-8;
t1=-2;
t2=4.
***************
Вернемся к обозначению x²+3x =t.
x²+3x =t1; =>x²+3x =-2.
x²+3x+2=0;
По т. Виета
x1+x2 =-3;
x1*x2=2;
x1=-2;
x2=-1.
--------------
x²+3x =t2; =>x²+3x =4.
x²+3x -4=0;
По т. Виета
x3+x4 =-3;
x3*x4=-4;
x3=-4;
x4=1.
Похожие вопросы
Предмет: Физика,
автор: Nigger8888
Предмет: Геометрия,
автор: kaumovmirzohid7
Предмет: Физика,
автор: lizasmirnova681
Предмет: Обществознание,
автор: mashamustafayeva04